The wadsworth casebook series for reading, research and writing : trifles - 195134 Kirszner, Laurie G.; Winchell, Donna Haisty; Glaspell, Susan, 1876-1948. Jury of her peers (Boston, MA : Wadsworth Publishing, 2004)
34